Effects of plyometric training direction on physical performance in basketball players - Aztarain-Cardiel, K.; López-Laval, I.; Marco-Contreras, L. A.; Sánchez-Sabaté, J.; Garatachea, N.; Pareja-Blanco, F. (International Journal of Sports Physiology and Performance, 2023)
Purpose: The aim of this study was to analyze the effects of plyometric training direction on jumping, sprinting, and change-of-direction ability in basketball players.